Radionuclide studies of left ventricular function in normal subjects - Wathen, C G; Muir, A L; Hannan, W J (Nuclear medicine communications, 1990)
The effects of age and exercise on cardiac function in a normal male population have been assessed by ECG-gated radionuclide ventriculography. Fifty-nine subjects aged from 25 to 54 years were studied (mean 44 +/- 10 S.D. years). Resting left ventricular ejection fraction (LVEF) was 0.54 +/- 0.07 and this increased by 0.07 +/- 0.05 during supine submaximal exercise at 75 watts. The mean increase in cardiac output on exercise was 93 +/- 30%. Stroke volume increased on exercise by 23 +/- 13% and end-systolic volume decreased by 10 +/- 16%. There was a weak correlation (P less than 0.05) between age and change in LVEF on exercise but the increase in cardiac output on exercise was not age dependent. It is important to use an age matched control population in any study of cardiac function.